Raltegravir pharmacokinetics during pregnancy - D. Heather Watts (2018)
Copyright © 2014 by Lippincott Williams & Wilkins. Objective: We evaluated the pharmacokinetics (PK) of raltegravir in HIV-infected women during pregnancy and postpartum. Methods: International Maternal Pediatric Adolescent AIDS Clinical Trials 1026s is an ongoing prospective study of antiretroviral PK during pregnancy (NCT00042289). Women receiving 400 μg raltegravir twice daily in combination antiretroviral therapy had intensive steady-state 12-hour PK profiles performed during pregnancy and at 6-to 12-week postpartum. Targets were trough concentration above 0.035 μg/mL, the estimated 10th percentile in nonpregnant historical controls. Results: Median raltegravir area under the curve was 6.6 μg h/mL for second trimester (n = 16), 5.4 μg h/mL for third trimester (n = 41), and 11.6 μg h/mL postpartum (n = 38) (P = 0.03 postpartum vs second trimester, P = 0.001 pp vs third trimester). Trough concentrations were above the target in 69%, 80%, and 79% of second trimester, third trimester, and postpartum subjects, respectively, with wide variability (<0.010-0.917 μg/mL), and no significant difference between third trimester and postpartum trough concentrations was detected. The median ratio of cord blood/maternal raltegravir concentrations was 1.5. HIV RNA levels were <400 copies per milliliter in 92% of women at delivery. Adverse events included elevated liver transaminases in 1 woman and vomiting in 1. All infants with known status are HIV uninfected. Conclusions: Median raltegravir area under the curve was reduced by approximately 50% during pregnancy; trough concentrations were frequently below target both during late pregnancy and postpartum. Raltegravir readily crossed the placenta. High rates of viral suppression at delivery and the lack of a clear relationship between raltegravir concentration and virologic effect in nonpregnant adults suggest that despite the decreased exposure during pregnancy, a higher dose is not necessary.